Prezgodnja menopavza - Meden-Vrtovec, Helena (Zdravniški vestnik, 2007)
Premature ovarian failure (POF) and connected problems are usually underestimated by the therapists. Precise analysis of etiology and adequate treatment enable resumption of reproductive function in some groups of the women with POF. Etiology of POF is heterogenous. It can be defined as genetic,autoimmune, iatrogenic, the rest presents as idiopathic. Among basic diagnostic procedures there are precise patient's history and determinations of FSH, LH, TSH, inhibin B, AMH (antimullerian hormone) concentration, kariotype and ACTH test. Additional procedures encomprise determinations of atherogenic factors (LDL, HDL, VLDL, hSCRP), determination of lenght of Q-T interval on standard EKG and immunologic investigations on cellular and humoral level. T'herapeutic possibilities include estrogen replacement treatment in case of idiopathic etiology and corticosteroid administration in case of autoimmune etiology of POF. Precise analysis of POF etiology enables specific treatment and resumption of reproductive function in some forms of POF (idiopathic and autoimmune).
Keywords: anamneza; diagnostika; Menopause, Premature; menopavza; Menopavza prezgodnja; prezgodnja menopavza; therapy; zdravljenje